Improving tuberculosis medication adherence: the potential of integrating digital technology and health belief model - Sazali, Mohd Fazeli; Syed Abdul Rahim, Syed Sharizman; Mohammad, Ahmad Hazim; Kadir, Fairrul; Payus, Alvin Oliver; Avoi, Richard; Jeffree, Mohammad Saffree; Omar, Azizan; Ibrahim, Mohd Yusof; Atil, Azman; Mohd Tuah, Nooralisa; Dapari, Rahmat; et al. (The Korean Academy of Tuberculosis and Respiratory Diseases, 2023)
Tuberculosis (TB) is a significant public health concern. Globally, TB is among the top 10 and the leading cause of death due to a single infectious agent. Providing standard anti-TB therapy for at least 6 months is recommended as one of the crucial strategies to control the TB epidemic. However, the long duration of TB treatment raised the issue of non-adherence. Non-adherence to TB therapy could negatively affect clinical and public health outcomes. Thus, directly observed therapy (DOT) has been introduced as a standard strategy to improve anti-TB medication adherence. Nonetheless, the DOT approach has been criticized due to inconvenience, stigma, reduced economic productivity, and reduced quality of life, which ultimately could complicate adherence issues. Apart from that, its effectiveness in improving anti-TB adherence is debatable. Therefore, digital technology could be an essential tool to enhance the implementation of DOT. Incorporating the health belief model (HBM) into digital technology can further increase its effectiveness in changing behavior and improving medication adherence. This article aimed to review the latest evidence regarding TB medication non-adherence, its associated factors, DOT’s efficacy and its alternatives, and the use of digital technology and HBM in improving medication adherence. This paper used the narrative review methodology to analyze related articles to address the study objectives. Conventional DOT has several disadvantages in TB management. Integrating HBM in digital technology development is potentially effective in improving medication adherence. Digital technology provides an opportunity to improve medication adherence to overcome various issues related to DOT implementation.